PENERAPAN METODE DESIGN THINKING PADA PERANCANGAN USER INTERFACE APLIKASI PPSU DKI JAKARTA BERBASIS MOBILE - Veronika Trinovianti (2023)
Penanganan Prasarana dan Sarana Umum DKI Jakarta (PPSU) is a work unit that works to manage roads, canals, parks, and cleanliness at the sub-district level based on Governor Regulation no. 7 of 2017. In Bambu Apus, East Jakarta, 79 PPSU officers are working under the coordination of the field coordinator. Every PPSU Officer is required to report the results of work activities that have been conducted at the end of the work shift to be collected to the field coordinator through the officer's daily performance report. Through this daily report, every day the field coordinator will receive seventy-nine reports to be processed into weekly reports and monthly reports which will then be forwarded as PPSU Performance Reports for Bambu Apus Village to the sub-district and city levels. The reports that have been collected have not been categorized and do not have specific reporting standards that regulate them. So, using the design thinking method, research was conducted to find out user needs and to design a mobile-based PPSU application as a solution to increase the effectiveness and efficiency of reporting the performance of DKI Jakarta PPSU Officers. Based on user needs, four primary features are designed, which are report collection features, report history, notifications, and accounts that are interrelated in managing daily performance reports collected by PPSU Officers. With the design features that have been made and then tested and measured usability values with the System Usability Scale (SUS) questionnaire, the average time needed to submit reports is 77.4 seconds with a final value obtained of 79.46. Based on the results obtained, it can be concluded that the target user can understand each feature in the application and is quite satisfied with the appearance of the planned application.